Wage differentials between the formal and the informal sector in urban Bolivia - Trine Mønsted (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2000)
This paper analyses wage differentials between the formal and informal sectors in urban Bolivia using household survey data. As in other studies the wage differential between the formal and the informal sector is found to be quite large. The wage gap is estimated by a human capital model correcting for selectivity bias using Heckman's two-step procedure. A surprising result is that migrants tend not be employed in the formal sector. Another noticeable result is that the probability of entering the formal sector was a hump shaped function of altitude probably because the government cities (La Paz and Sucre) are located at mid altitudes. The wage generating processes for the two sectors are quite different, and the results indicate that productivity is relatively more important for wages in the informal sector than in the formal sector. It is also found that returns to education are generally higher for formal sector workers. In a non-linear specification of returns to schooling the conclusion is that basic education is not rewarded in the labour market, therefore seriously questioning the quality of the educational system. An Oaxaca decomposition of the wage differential between the two sectors shows that there are differences in characteristics between formal and informal sector workers, but these characteristics are also rewarded differently in the two sectors. The analysis also confirms that education and experience are the main factors contributing to the wage differentials between sectors.
Keywords: Q23; Q28; R12; R14; 330; Amazon deforestation; carbon emissions